An analysis of the engagements of intellectuals and intellectual activity in the South African media: a case study of the Native Club - Masango, Philile (My University, 2010)
ABSTRACT The primary aim of this study was to investigate how, and in what ways, the issue of intellectuals and intellectual activity is engaged in the media, specifically by investigating what issues were raised in the media by the formation of the Native Club in 2006. I examined how issues about the Native Club entered public debate through the media and which individuals spoke in the debate. To fulfil the objectives of the research, I mapped and analysed writings on the topic in the mainstream, commercial English and Afrikaans newspapers as well as other text-based media forums, such as websites, for a period of three months from the inception of the Native Club. I then used interviews and text analysis to answer the primary question of the research. By drawing on media theories such as agenda-setting, I also sought to answer questions about the mechanisms by which the debate entered into and stayed in the media, as well as how these debates were framed. The findings of this research reveal that although some newspapers did not cover the Native Club at all, in the more educated and affluent Afrikaans and English-language newspapers, media engagement with the issue was extensive, suggesting that this sector of the media was widely available as a space for public deliberation. However, the findings reveal that this did not necessarily translate to the media being able to fulfil all of their responsibilities as a tool for participatory democracy, because they failed to question and bring out some of the contentious issues about the Native Club, such as its perceived link to the office of the president of South Africa and its funding by the government. Another key finding was that although the local debate around intellectual issues was generally in line with global trends, and reflected similar positions in the contestation about who is an “intellectual”, the role of the intellectual in society, and which position they should speak from, South Africa’s case was somewhat peculiar in the sense that definitions of intellectuals go beyond their capabilities, role and positions, into what race they are. The study concludes by acknowledging that the question of intellectual activity is considered significant and remains high on the South African media agenda, and extensive coverage is given to it, but that, drawing from the findings, certain South African intellectuals feel there is a need for an alternative public sphere (like the Native Club) other than the media. However, there seems to be no agreement on how an ideal public sphere would operate.